THE EFFECTIVENESS OF PROBLEM - BASED LEARNING MODEL LEARNING DEVICES - Lismayuni Lismayuni; Vandalita MM. Rambitan; Sonja VT Lumowa (Program Pascasarjana Universitas Negeri Jakarta, 2020)
The purpose of this study is to find out what problems are faced by teachers when developing a Problem based learning (PBL) model of learning tools to improve student's critical thinking skills. This research was conducted at SMAIT Daarul Hikmah Bontang class X 1 and X 2. The sample of this study was 25 teachers in the school, the sample of this study was 5 teachers who taught exact subjects. Primary data collection using observation sheets related to Problem based learning (PBL) Model learning devices containing 25 questions. The results of the study show problems related to compiling learning tools through a problem-based learning model(PBL) it was found that some teachers had problems with references and did not understand learning models that were relevant to learning materials in schools, assessment instruments as supporters related to the problems faced when compiling a problem-based learning (PBL) model of learning tools. 80% of student learning outcomes experienced a more significant increase after using the problem-based learning (PBL) model.